An induced pluripotent stem cell-based approach for hair follicle development and regeneration - Poornima Sivamani; Ramya Lakshmi Rajendran; Prakash Gangadaran; Byeong-Cheol Ahn (Regenerative Therapy)
Because hair loss is a common concern for many individuals, potential regenerative therapies of hair follicles have been extensively researched. Induced pluripotent stem cells (iPSCs) are a promising avenue for hair follicle regeneration. This review explores current iPSC-based approaches and highlights their potential applications and challenges in hair restoration. The principles of iPSC technology, iPSC differentiation into hair follicle precursor cells, and potential clinical implications for hair follicle regeneration are also discussed. This overview of iPSCs and their applications aims to contribute to our understanding of their role in hair restoration and potential future therapeutic applications.